Law No. 2 of the Year 2025 Amending Certain Provisions of Law No. 232 of the Year 1989 On Ships Safety = قانون رقم 2 لسنة 2025 بتعديل بعض أحكام القانون رقم 232 لسنة 1989 فى شأن سلامة السفن - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic